Reversible and pH-modulated changes in microgel size triggered by electrochemical stimuli. (December 2022) - Marcisz, K.; Jagleniec, D.; Mackiewicz, M.; Romanski, J.; Karbarz, M.
Abstract: A novel microgel, the volume of which can be reversibly changed by using an electrochemical trigger, was successfully synthesized. To this end, a monomer based on N -(3-aminopropyl)methacrylamide modified with ferrocenecarboxylic acid was obtained and co-polymerized with acrylic acid and N, N ′–methylenebisacrylamide. Using the distillation precipitation polymerization method, spherical, smooth-surfaced microgel particles ca. 500 nm in diameter were obtained. The presence of ferrocene groups in the microgel was shown with nuclear magnetic resonance spectroscopy, energy dispersive X-ray spectroscopy, and cyclic voltammetry methods. Dynamic light scattering experiments showed that the microgel size strongly depends on the oxidation state of the ferrocene groups. Next, cyclic voltammetry and chronoamperometry combined with quartz crystal microbalance measurements, obtained with an Au electrochemical quartz crystal microbalance electrode modified with the microgel, proved that the microgel size could be controlled by an electrochemical trigger. More interestingly, the electro-response was found to strongly depend on pH. In acidic pH, where almost all carboxylic groups are protonated, the oxidation of ferrocene groups led to a decrease in the registered frequency shift, related to the microgel swelling process. In alkaline pH, where many carboxylic groups are ionized, the oxidation of ferrocene led to an increase in frequency, related to the microgel shrinking process. These processes were found to be reversible and relatively fast. Graphical abstract: Image 1 Highlights: A new pH sensitive and electrosensitive microgel was synthesized. The microgel dimensions could be altered by an appropriate potential. The electro-response strongly depends on pH. The electro-response is reversible and relatively fast.